Floristic inventory and vegetation of the crater of the Alberca de Teremendo, Michoacán, Mexico - Contreras León, Jesus; Silva Sáenz, Patricia (Instituto de Ecología, A.C., 2020)
Background and Aims: The crater of the Alberca de Teremendo de los Reyes, Morelia municipality, is one of the three volcanic lakes that exist in Michoacán, Mexico. Currently, it only has research focused on the study of water quality and algae, but it lacks a floristic inventory. The objectives of this study were to prepare a list of its vascular flora and describe its vegetation.Methods: Twenty-seven field trips were conducted between October 2013 and September 2015, collecting plant material recording habitat, vegetation and biological form of the species. Vegetation was described regarding its composition, structure and location. The taxonomic biodiversity index was calculated to define species richness per hectare compared to other regional studies.Key results: A list of 316 plant species of plants and 12 infraspecific taxa is presented, belonging to 228 genera and 85 families. The most plants diverse family was Asteraceae with 39 species (12.3% of the total); at the generic level it was Euphorbia with seven species (2.2%); herbaceous dominate with 235 taxa (74.1%). The vegetation is described as subtropical scrub plant community, which is best represented by the area that covers approximately 57.3 ha, associated with elements of tropical deciduous forest, aquatic and underwater vegetation, grassland and ruderal plants.Conclusions: The study area has 3.8% of the species registered for the state and 2% of those of the municipality. It has the highest generic and specific affinity (63.9 and 38.8%, respectively) with the Quinceo hill. The Alberca de Teremendo crater stands out floristically, since in a limited area (108 ha), it houses a vast flora with 67.6 species per ha. Three species are in the NOM-059-SEMARNAT-2010: one in the Threatened category (Erythrina americana) and two Subject to special protection (Gentiana spathacea and Cedrela odorata).